Metachronous Occurrence of Triple Malignancies of Kidneys, Prostate, and Breast. A Case Report and Review of The Literature - Mohammad Ali Zargar-Shoshtari; Hossein Saffari; Mohammad Kazem Moslemi (Case Reports in Urology)
Multiple consecutive cancers involving different organs in a male individual are presented. Case Presentation. Herein, we present a rare case of primary right renal cell carcinoma (RCC), in which two different organ malignancies of prostate and breast were occurred consecutively. After proper treatment of each organ tumor, the patient experienced metachronous occurrence of its final tumor in his remained left kidney as left side RCC. Discussions. Multiple primary cancers are defined as occurrence of two or more malignancies, synchronous or metachronous, in different organs without any relation to each other. For primary and secondary tumors of the male genitourinary system, the most common occurrence was tumors of bladder and prostate followed by tumors of the kidney. Our case was a rare presentation of consecutive occurrence of multiple organ tumors: right side RCC, adenocarcinoma of prostate, and ductal cell carcinoma of the left breast, followed by left side RCC. Conclusions. In any case of primary malignancy of any organ, not only primary tumor recurrence but also tumoral growth of other nonrelated organs should be evaluated, especially in high risk patients or patients with positive familial history.